Interannual Nearshore Habitat Use of Young of the Year White Sharks Off Southern California - Anderson, James M.; Burns, Echelle S.; Meese, Emily N.; Farrugia, Thomas J.; Stirling, Brian S.; White, Connor F.; Logan, Ryan K.; O’Sullivan, John; Winkler, Chuck; Lowe, Christopher G. (Frontiers in Marine Science, 2021)
Young of the year (YOY) and juvenile-stage white sharks may use southern California nearshore beach habitats more extensively than previously known, within meters of some of the most heavily used beaches in the world. Such knowledge forms a critical component of species management and conservation plans, in addition to public safety and risk mitigation planning. We used data derived from a combination of satellite tag locations (13 animals over 3 years) and passive acoustic monitoring (44 animals over 8 years) to examine the occurrence, density and residency patterns of YOY white sharks in southern California waters. Our results suggest that southern California contains spatially dynamic centers of primary nursery habitat. Individuals exhibited temporal fidelity, higher levels of residency, and spatially restricted movements while resident in these locations. There was spatio-temporal overlap amongst individuals, with multiple YOY individuals simultaneously displaying this behavior. These animals formed loose aggregations at ‘hotspot’ locations that were interannually variable. Models of biotic and abiotic variables were unable to identify consistent predictors of shark occurrence and residency. Thus, novel approaches that incorporate technologies to derive high resolution in situ data, paired with more comprehensive telemetry datasets are therefore required to better understand the extrinsic factors that drive habitat selection and residency patterns in juvenile white sharks.